Effect of Antitranspirant Phenylmercuric Acetate on some Conifer Seedlings-a Preliminary Study - Guhathakurta, P. (Indian Forester, 1973)
Excessive transpiration and resultant mortality of seedlings at the time of planting is one of the most important physiological problems associated with afforestation. An anti-transpirant, Phenylmercuric acetate which acts as a metabolic inhibitor and preveats stomatal opening has thrown up promise of maintaining a favourable water balance in transplant seedlings. The present study investigates the effect of Phenylmercuric acetate on transpiration in 11 month old nursery seedlings of Pinus patula Schidede and Deppe and Pinus taeda Linn. dripped in the chemical for 1 hour. In the case of conifers, the stomata being sunken, it is extremely difficult to observe the efficacy of this chemical in relation to stomatal opening. In an indirect method, the weight of seedlings was measured al percentage of initial green weight and expressed as a function of time upto the 6th day. In Pinus patula the rate of loss of water in 5000 ppm treated seedlings has been the least. In 500 ppm the response has appeared late, but the trend of drying out has heen slower than 5000 ppm. There was no effect with 100 ppm. In Pinus taeda both 100 ppm and 500 ppm treated seedlings have shown a slower rate of loss of water than the control. With 5000 ppm treatment the rate of loss of water has been faster than either control or other treatments. This high concentration treatment had adverse side effects in both Pinus patula and P. taeda but in a more pronounced way in the latter.